KOMPETENSI PROFESIONAL GURU SMA KALAM KUDUS MEDAN - Charles Fransiscus Ambarita (PGSD Universitas Negeri Medan, 2017)
This research aims to find the relationship between the professional competence of teachers and work discipline. Sample of research is 5 teachers of Kalam Kudus School Medan. Data collection techniques by questionnaire and documentation method. Based on the data, from 5 respondents who get below average score are 1 person, while those who get score between top and bottom average are 3 people and who get above average is 1 person. This means that high school teachers of Kalam Kudus has known and implement the teacher professionals in teaching and learning process in class and Kalam Kudus School Medan. Key Words: Professional Ability and Work Discipline